Women in Otorhinolaryngolgy in Nigeria - Adebola, Shofoluwe Nurudeen; Jamila, Lawal; Rasheedat, Sanni; Abdulrahman, Afolabi Olushola; Bello, Fufore Mohammed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Surgery has a predominantly male-dominated population, especially in Otolaryngology. Efforts have been made worldwide to improve gender equality in medicine, including Otolaryngology. Knowing the experience will help the curriculum develop. Methods: An anonymous web-based survey was distributed via the WhatsApp group of the Otorhinolaryngological Society of Nigeria (ORLSON) platform using the survey monkey. A questionnaire-based study using a 10 stem questions, assessing demographics, academic progression, work life balance and factors affecting women in Otolaryngology in Nigeria was carried out in April 2020 for four weeks. All information gathered from the study was entered into Statistical Package and Service Solution (SPSS) version 20 and analyzed. Results: A total of 37 women responded out of 48 women in Otolaryngology practice. Twenty-nine (78%) had complete responses to all the ten stem questions. Mean age of responders is 39±7.28 years ±7.27 S.D. Thirty-eight percent are consultant cadre, 86% are married. The average duration of residency is 7 years. A quarter of responders are interested in Head and Neck as a subspecialty. Thirteen-point eight percent experienced some form of sexual harassment during the course of residency training, 62% believe women lack mentorship in Otolaryngology while 59.46% did not feel disadvantaged as females in otolaryngology compared to their male counterparts. Conclusions: Despite increase in women in surgical practice and a growing number of women joining residency programs, the number of female Otolaryngologists remains just a fraction of what it should be. The curriculum has many problems affected by gender.